Development of engineering solutions for air drilling at Dulisminsk oilfield, Irkutsk oblast; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Boyarko Yu. L. Yuriy Leontievich (Latest Technology of Oil and Gas Driling, 2015)
Title screen